2017
DOI: 10.1111/edt.12313
|View full text |Cite
|
Sign up to set email alerts
|

Removal of a large number of foreign bodies in the maxillofacial region with navigation system

Abstract: The removal of a large number of foreign bodies in the maxillofacial region can be complicated and challenging. In this case report, a specific strategy for removal of multiple foreign bodies in the maxillofacial region is presented. A girl diagnosed with 24 foreign bodies in her left lower face and neck underwent the surgery using a computer-assisted navigation system. A specific strategy was used in this case, which included from one sub-region to the next and from the easiest to the most difficult. This str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In this respect, foreign body fragments that are asymptomatic and those located close to vital structures are removed to prevent further complications such as foreign body reaction, infections, sinusitis, possible metal poisoning and meningitis. 7,15 Santos et al 16 reported two cases of foreign body ingestion during dental implant procedures, with neither patients showing any signs nor symptoms. However, one of the patients required removal of the impacted foreign body from the intestinal region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, foreign body fragments that are asymptomatic and those located close to vital structures are removed to prevent further complications such as foreign body reaction, infections, sinusitis, possible metal poisoning and meningitis. 7,15 Santos et al 16 reported two cases of foreign body ingestion during dental implant procedures, with neither patients showing any signs nor symptoms. However, one of the patients required removal of the impacted foreign body from the intestinal region.…”
Section: Discussionmentioning
confidence: 99%
“…4 In the maxillofacial regions, the removal of foreign bodies is required in cases of potential airway obstruction and in order to mitigate the chance of post-operative infections or damage to soft tissues. 7,8 The location and retrieval of orthodontic bands and brackets represent a challenge for the maxillofacial surgeon. [3][4][5][6][7] In this context, surgical navigation is a very promising addition to the surgical toolkit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of FBs were broken needles, metal fragments or projectiles, and located in the craniofacial area, which is a complex anatomic zone and has numerous vital or delicate structures. Only four papers reported about the removal of firearm projectiles and shrapnel [16,24,27,32]. With the help of CSN, all FBs in the 20 papers were successfully located and removed, with or without assistant method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Importantly, it allows the "fusion" of the surgical gesture with imaging data, improving accuracy, especially in the presence of delicate structures. Many studies have reported the CSN-guided removal of FB from the human body, especially in the complex and delicate craniomaxillofacial area [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. CSN is helpful in determining the location of FB, determining the optimal surgical approach, minimizing iatrogenic damage, and reducing the operation time.…”
Section: Introductionmentioning
confidence: 99%